Sagaria 1-8: ‘n Algemene oorsig - O’Kennedy, DF (Nederduitse Gereformeerde Teologiese Tydskrif, 2008)
There is a renewed interest in the book Zechariah, the second last in the Book of the Twelve. Several prominent commentaries were published in the last decade: Hanhart (1998); Floyd (2000); Sweeney (2000); Clark & Hatton (2002); Merril (2003); Boda (2004); O’Brein (2004); etcetera. This is the first of two articles on the book of Zechariah and focuses on chapters 1-8 or Proto-Zechariah. The aim of the article is to provide a general survey of Zechariah 1-8 and the major issues are discussed under the following headings: Relationship with the rest of the Bible; Unity of the book; Authorship, dating and socio-historical background; Structure and division; Literary features; Theological message. Proto-Zechariah is one of the most diverse and interesting books in the Old Testament. In some instances the message is clear with precise historical detail while in other passages the message is mysterious with several visions and symbols. Zechariah 1-8 had a message for the post-exilic community in Yehud/Judah and it has a message for the people of South Africa that live in a time of reconstruction and development. Therefore, the study of this book cannot be neglected.